Histochemical study of asbestos fibre coating in experimental carrageenin granulomas. Issue 3 (July 1973) - Governa, M.; Vadalà, C. Rosanda
Abstract : Governa, M., and Rosanda Vadalà, C. (1973). British Journal of Industrial Medicine, 30, 248-252. Histochemical study of asbestos fibre coating in experimental carrageenin granulomas. To study the composition of asbestos body coating, asbestos particles present in experimental carrageenin granulomas were tested histochemically for mucopolysaccharides, ferric and ferrous iron, haemoglobin, and haematoidin. The stains were applied on microscopical sections both untreated and treated with iron-extracting solutions and/or enzymes. The results indicate that asbestos is rapidly coated with haematoidin, ferric iron, and hyaluronic acid.